THE DUAL ROLE OF SOCIAL MEDIA IN SHAPING ADOLESCENT DIETARY KNOWLEDGE AND ATTITUDES: EVIDENCE FROM A SEMI-RURAL DISTRICT IN INDONESIA - Dahlia, Besse; Ibrahim, Muh. Siddik; Alwi, Juwitriani (UNG, 2026)
Social media platforms have become dominant sources of food-related information among adolescents, shaping dietary knowledge, attitudes, and consumption behavior. However, evidence from semi-rural settings in Indonesia remains limited. This study aimed to examine the influence of social media exposure on adolescent dietary knowledge and attitudes in Pasarwajo District, a semi-rural area of Southeast Sulawesi, and to explore its implications for health promotion. A mixed-method cross-sectional design was employed involving 100 adolescents aged 15–18 years who were active social media users. Quantitative data were collected using structured questionnaires and analyzed using descriptive statistics and Fisher’s exact test, while qualitative data from in-depth interviews with 15 adolescents were analyzed thematically. The results showed that daily social media use was significantly associated with higher nutritional knowledge (p = 0.021) and more positive attitudes toward healthy eating (p = 0.039). Female adolescents demonstrated more favorable attitudes than males (p = 0.038). Qualitative findings revealed a dual influence of social media, combining exposure to health-promoting content with frequent fast-food promotions, while family remained an important non-digital influence. This study offers contextual novelty by demonstrating that in a semi-rural Indonesian setting, social media may function not only as a risk factor but also as a complementary channel for strengthening adolescent nutritional awareness when supported by family and school environments. These findings highlight the importance of integrating digital and community-based strategies in adolescent health promotion.